Analisis Variabel-Variabel yang Memengaruhi Kesejahteraan Pekerja Lansia Berstatus KRT di Provinsi Nusa Tenggara Timur Tahun 2022 - Yendri, Rahma Zikra; Prasetyo, Achmad (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2024)
Most countries in the world are currently experiencing the phenomenon of population aging, and Indonesia is no exception. Since 2021, Indonesia has entered the old population structure. Population aging is a development challenge due to the vulnerable and unwell elderly, especially those who work. Nationally, East Nusa Tenggara (NTT) Province is the province with the highest percentage of working elderly above the national figure and among them are at the bottom of the economy. Therefore, this study aims to determine the variables that affect the welfare status of the working elderly household head. By using Susenas data in 2022 and the multilevel binary logistic regression method, it was found that as many as 40.15 percent of the welfare status of the working elderly household head in NTT Province were classified as not prosperous. Then, the variables of age, gender, regional classification, education, marital status, pension insurance ownership, and cellphone usage at the individual level, as well as the variables of health facility ratio, and crime incidence ratio at the district/city level have a significant effect on the welfare status of the working elderly household head in NTT Province. The tendency for the elderly to be unwell is greatest for the elderly who are female, live in rural areas, have completed primary school, have never married, do not have pension insurance, do not use mobile phones, have a low ratio of health facilities in districts/cities, and a high ratio of crime incidents in districts/cities. The variation in the welfare of the elderly with head of household status caused by differences in the characteristics of each district/city is 4.56 percent.